The Effectiveness of Play-Based Learning Methods in Improving Basic Badminton Serve Skills among Senior High School Students: Efektivitas Metode Pembelajaran Berbasis Bermain dalam Meningkatkan Keterampilan Servis Dasar Bulu Tangkis Siswa SMA - Komang Sukma Veralia; Didik Purwanto; Gunawan Gunawan (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
This classroom action research aimed to improve students’ basic badminton service skills through a play-based learning approach in Class X E of SMA Negeri 4 Palu. The study was conducted in two cycles following Kemmis and McTaggart’s CAR stages: planning, action, observation, and reflection. Service skills were assessed using an analytic rubric covering stance/preparation, swing/contact, shuttle direction accuracy, and follow-through; supporting qualitative data were collected from structured observation notes. Individual mastery was set at a minimum score of 70, while classical mastery was achieved when ≥85% of students reached this threshold. Pre-cycle results showed 10 of 30 students (33.3%) met mastery. After Cycle I implementation (target-serve games and relay-serve games), mastery rose to 19 of 30 (63.3%). Revisions in Cycle II (greater target variability, paired consistency drills, additional guided practice, and self-modeling homework) increased mastery to 25 of 30 (85.0%), meeting the success indicator. The findings indicate that play-based learning improves service performance by increasing meaningful repetitions, immediate feedback, and competitive engagement in physical education classes.